Design of Array MEMS Vector Vibration Sensor in the Location of Pipeline Inspection Gauge - Mengran Liu; Guojun Zhang; Zeming Jian; Hong Liu; Xiaopeng Song; Wendong Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In view of the pipeline marking difficult and poor measurement precision, a new-type monolithic integrated array MEMS vector vibration sensor has been put forward. It has overcomed the deficiency that present vector acoustic sensor applied in the oil and gas pipeline inspection gauge can not be accurate about signal position, and eliminated the port/starboard blur problem. Through ANSYS simulation analysis, it conclude that the array vector vibration sensor has the sensitivity of 2.05mv/pa (-173.8dB,0dB=1v/μpa). The first-order modal is 438 Hz, and the third-order modal is 452 Hz. The resonance frequency of the two sensitive components is respectively 452 Hz and 438 Hz. At the end of this paper , the algorithm that can be used to estimate the azimuth angle detected by the sensor , is given.